The Influence Of The Constitutional Court Decision Against Combating Money Laundering In The Context Of Criminal Law Reform - Somawijaya -; Ajie Ramdan (The Constitutional Court of the Republic of Indonesia, 2015)
According to Moeljatno, Criminal Law is a part of a country’s legal system that prohibits certain acts with the threat of sanction for those who break said laws, determines when and in what cases such punishments should be imposed upon those who commit said acts and determines precisely how punishments should be carried out in the event that a person is accused of such acts. This paper will analyse Constitutional Court Decision No. 77/PUU-XII/2014 and Decision No. 21/PUU-XII/2014 regarding Criminal Law reform. Looking to the theory of procedural criminal law, an indictment of cumulative charges of money laundering requires that the underlying predicate offences be proven. If, for example, the predicate offence is corruption, the corruption must be proven as multiple crimes have been committed by the same suspect, namely corruption leading to money laundering. the Decision of the Pretrial Judge of the Court of South Jakarta, Sarpin Rizaldi, and Constitution Court Decision No. 21/PUU- XII/2014 on the review of Article 77 of Act No. 8 Year 1981 concerning the Law of Criminal Procedure broadened the range of pretrial objects and greatly affected the principles of formal criminal law.